Pengaruh Penggunaan Metode Multisensori dan Media Flashcard terhadap Peningkatan Kemampuan Pramembaca Anak - Widya Tri Utomo; Linda Ardiya Waroka; Andhika Djalu Sembada (Ideas Publishing, 2023)
Pre-reading abilities in children can influence their development process and multisensory techniques and flashcard media are the right choices to improve the quality of children s pre-reading. This technique can help children who do not have pre-reading skills to develop better. The research method used is quantitative with a descriptive analysis concept. Based on data obtained from the use of multisensory techniques and flashcard media, the SPPS calculation results have a significance value of 0.006 which means less than 0.05. This means that it is proven that there is an influence on beginner reading skills. Therefore, these two methods have a significant effect on children s pre-reading abilities, so that each method has its own uniqueness, and is able to arouse children s learning enthusiasm while participating in the learning process.